Effects of Self-Weighing During Weight Loss Treatment: A 6-Month Randomized Controlled Trial - Hernández-Reyes, Alberto; Cámara-Martos, Fernando; Vidal, Ángela; Molina-Luque, Rafael; Moreno-Rojas, Rafael (Frontiers in Psychology, 2020)
Objective: To examine the effectiveness of self-weighing for weight loss in men for 6 months. Methods: In the present study, 54 men, mean age of 40.1 ± 11.1 years, with overweight or obesity, were recruited and randomly assigned into two groups: control group (CG), without weight self-monitoring and intervention group (IG), with weight self-monitoring. Both groups received the same nutritional and educational advice and the establishment of a weight target to reach in the weight loss program. Subjects of IG also had individualized motivating content to improve self-management for 24 weeks. Anthropometric indices were measured at baseline and weekly for 24 weeks. Results: When the group assigned after randomization was introduced in the analysis, its influence was significant in weight loss (F1.52 = 19.465, 2 = 0.272, p <0.001) and in the decrease in body fat percentage (F1, 52 = 8,306,  2 = 0.132, p <0.01). Conclusion: Study results indicate that self-weighing can help patients to lose additional weight. Our findings have implications in the emerging area of the behavioral approach of patients undergoing weight-loss treatment, as well as clinical care processes